Case studies in knowledge management - Jennex, Murray E. 1956- (Idea Group Pub., 2005)
Case Studies in Knowledge Management provides case-based lessons learned from several examples of actual applications of knowledge management in a variety of organizational and global settings. A variety of KM issues are explored, including issues associated with building a KMS, organizational culture and its effect on knowledge capture, sharing, re-use, strategy, and implementation of KM initiatives and a KMS. The benefit of focusing on case and action research is that this research provides an extensive and in-depth background and analysis on the subjects, providing readers with greater insight into the issues discussed.